Development of project success model using partial least squares - structural equation modeling for Malaysia SMES - Khan, Ahmed Ali M. (2019)
Globalization and hyper-competitive business environments have forced organizations, large businesses, and Small and Medium-sized Enterprises (SMEs) alike, to define and undertake organizational projects to improve their products, services, market position, or processes. Despite recent advancements in the project management practices and tools, the rate of project success among organizations, SMEs in particular, has worryingly remained low. Since SMEs play a vital role in the economic development of Malaysia, it is crucial to assist Malaysian SMEs with improving the success rate of their projects and achieving higher corporate competitiveness and survivability. Consistently, the present study attempted to address this research gap by developing a model of project success among Malaysian SMEs. In doing so, the study first benefited from the Interpretive Structural Modelling (ISM) approach to identify project success factors most critical to SMEs. The study achieved this objective by performing a content-centric review of literature that identified 11 project success factors of employee qualification, employee development and training, information and digital technology competency, knowledge management, organizational culture, organizational structure flexibility, project management competency, project performance measurement, resource allocation efficiency, risk management, and top management support and commitment. After capturing the opinions of a group of Malaysian project management experts, the ISM approach identified the precedence relationships among the 11 success factors and produced the model of project success among SMEs. This model was further statistically tested among a sample of 142 Malaysian SMEs. The application of Partial Least Squares (PLS) structural equation modelling (SEM) for data analysis revealed the statistical significance and magnitude of the precedence relationships identified within the ISM model. The assessment of PLS model of project success among Malaysian SMEs demonstrated that complex precedence relationships exist among project success factors. The achievement of project success is not accidental, and Malaysian SMEs should strategically plan their efforts and resource in support of project success. It means achieving the highest rate of project success depends significantly on the order and quality under which SMEs develop project success factors. Findings indicated that project success accounted for more than 25 percent of the variance in business performance among surveyed SMEs. This finding shows that project success leadership, defined as excelling in project effectiveness and efficiency, has been a valuable and affordable business strategy to Malaysian SMEs, which has the potential to provide the implementing firms with superior competitiveness and business performance improvement. Finally, yet importantly, the present study develops and offers a project selection software that enables SMEs to look at their existing success factors and select the best project option that has the highest chance of success rate.